Improving competition in the non-tradable goods and labour markets : the Portuguese case - Almeida, Vanda (2018)
This study assesses the macroeconomic impacts of increasing competition in the non-tradable goods and labour markets in Portugal. We lean on evidence that the maintenance of low competition in these markets may have contributed to the recent poor performance of the Portuguese economy. The analysis is performed using PESSOA, a dynamic general equilibrium model for a small-open economy integrated in a monetary union, featuring non-Ricardian characteristics, a multi-sectoral production structure and a number of nominal and real rigidities. We conclude that measures aimed at increasing competition in the Portuguese non-tradable goods and labour markets could induce important international competitiveness gains and be valuable instruments in promoting necessary adjustments within the monetary union framework. However, in the short run, real interest rates are likely to increase, driving consumption and output temporarily downwards.